Recent Researches in the Geology of Northwest West Paksiatn - Jan, M. Qasim; Kempe, D.R.C (Journal of Himalayan Earth Sciences, 1970)
The northwest part of West Pakistan has seen detailed geological investigation in several areas during the past ten years. In this paper, an attempt has been made to give a brief account of the research work (much of which has already been published) carried out in Peshawar and Malakand Divisions, and in Gilgit Agency since 1947. A summary of economic investigations is given and a detailed account of the bibliography has been presented in the end to provide an easy source of references for future workers. The important conclusion that the authors have reached from this work is that many of the more or less regionally metamorphosed rocks, previously considered Precambrian, are mainly Siluro-Devonian and, to a lesser extent, Carboniferous in age, with a relative abundance of reef complexes. Many of these rocks were intruded by various types of igneous rocks (mainly granites), mostly during the Late Creraceous and Early Tertiary periods.